STRENGTHENING NATIONAL CHARACTER EDUCATION IN CIVICS EDUCATION LEARNING AS AN EFFORTS TO PREVENT STUDENT BRAWLING AT STATE SENIOR HIGH SCHOOL 14, SABATANG VILLAGE SOUTH HALMAHERA REGENCY - Jainudin Abdullah; Rustam Hasim; Mukhtar Yusup (SOSIOEDUKASI, 2026)
Globalization and the development of information technology have impacted changes in adolescent behavior, including an increase in social conflicts between students that have led to brawls. This phenomenon also occurred at State Senior High School 14, Sabatang Village, South Halmahera, and was influenced by low emotional control skills, the influence of social circles, and students' lack of understanding of peaceful conflict resolution. Yet, Civics Education (PKn) learning plays a strategic role in instilling national character values ​​that can prevent violent behavior. This study aims to (1) determine the implementation of strengthening national character education through civics learning, and (2) determine the character values ​​instilled through civics learning in an effort to prevent student brawls at State Senior High School 14, Sabatang Village, South Halmahera. This study uses a qualitative research method with a descriptive approach. Data collection techniques are carried out through interviews, observation, and documentation, while data analysis is carried out through data reduction, data presentation, and drawing conclusions. The research results indicate that (1) the implementation of strengthening national character education is carried out through the integration of character values ​​in the planning and implementation of Civics learning, using discussion methods, case studies, group work, and the habituation of positive attitudes through school activities involving teacher role models and the implementation of school regulations. (2) The instilled character values ​​include discipline, responsibility, tolerance, self-control, legal awareness, mutual respect, and a love of peace, which play a role in shaping students' moral and social awareness so that they are able to resolve conflicts through deliberation and avoid violent behavior.